Ecofriendly Management Of Pod Borer Complex On Pigeonpea (Cajanus Cajan) (Journal of Plant Disease Sciences, 2020)
The field experiment was conducted during kharif 2013-14, in randomized block design with four replications.Total six treatments viz.,Metarhizium anisoplea (108) 4g/L, Beauveria bassiana (108) 4g/L, NSE 5% 50g/L, Azadirachtin 1500 ppm 5ml/L, Emamectin benzoate 5 SC 0.5g/L and Untreated control were studied. There were three applications given during entire period of experiment. The observation on larval reduction of pod borer complex and pod damage was recorded at 3, 7 and 10 days after each applications and the cumulative effect of all applications has been reported. The treatment Emamectin benzoate 5 SC 0.5g/L emerged out as the most superior one against Pigeonpea pod borer complex in reducing the larval population and pod damage. Beauveria bassiana (108) 4g/L and Metarhizium anisopliae (108) 4g/L also performed better and emerged as next effective treatments against this pest complex and recorded significant reduction in larval population and pod damage.The application of NSE 5% 50g/L least promising in reducing the larval population of pod borer complex as well as pod damage followed by the application Azadirachtin 1500 ppm 5ml/L.
Keywords: Beauveria bassiana; Metarhizium anisopliae; Pod borer complex